Light and efficient wave-absorbing material based on water-absorbent resin and preparation method of light and efficient wave-absorbing material

By using water-absorbing resin and cobalt salt aqueous solution to prepare Co/C composite wave absorbing materials, the problem of absorbing materials taking into account lightweight and efficient wave absorbing efficiency is solved, and the effects of strong electromagnetic wave attenuation and lightweight stability are achieved. Green and environmentally friendly processes reduce production costs and are suitable for a variety of application scenarios.

CN119255582AActive Publication Date: 2025-01-03NAT UNIV OF DEFENSE TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411209307.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-03
Estimated Expiration
2044-08-30

AI Technical Summary

Technical Problem

Existing absorbing materials are difficult to balance between lightweight and efficient absorbing efficiency, and there are environmental protection and cost problems in processing and production processes, which cannot meet the needs of multiple application scenarios.

Method used

The water-absorbing resin is used as the precursor to form a Co@ organic resin composite material by absorbing the aqueous cobalt salt solution, and pyrolyzed at a certain temperature to obtain the Co/C composite wave absorbing material. The materials prepared by this method have strong electromagnetic wave attenuation ability and light weight and stability, and the absorption band can be regulated by regulating the pyrolysis temperature and cobalt salt concentration.

Benefits of technology

It achieves efficient and lightweight electromagnetic wave absorption capacity, strong plasticity of materials, environmentally friendly preparation process, low cost, suitable for large-scale mass production, and can be used for electromagnetic protection of a variety of equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119255582A_ABST
    Figure CN119255582A_ABST
Patent Text Reader

Abstract

The invention discloses a lightweight and efficient wave-absorbing material based on water-absorbent resin and a preparation method thereof, and relates to the technical field of C-X wave band wave-absorbing materials. The preparation method comprises the following steps: S1, preparing a cobalt salt aqueous solution with the concentration of 2-6g / L, and standing and soaking water-absorbent resin in the cobalt salt aqueous solution until the color of the solution becomes colorless to obtain a Co-coated resin composite material; wherein the mass ratio of the water-absorbent resin to the cobalt salt is (4-6): (1-3); and S2, pyrolyzing the Co-coated resin composite material, and then naturally cooling to obtain the Co / C composite material. The Co / C composite wave-absorbing material obtained by the method has the advantage of strong electromagnetic wave attenuation capability, and also has the characteristics of light weight and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of CX-band absorbing materials, and in particular relates to a light-weight and high-efficiency absorbing material based on a water-absorbing resin and a preparation method thereof. Background Art

[0002] Wave-absorbing materials have a wide range of application needs in the fields of military stealth technology, electromagnetic compatibility of electronic equipment, radiation protection of wireless communication base stations, and electromagnetic shielding of buildings. For example, wave-absorbing materials can effectively absorb radar waves, helping military equipment such as aircraft and ships to reduce radar reflection signals and improve stealth performance; wave-absorbing materials can be used for electromagnetic shielding of electronic equipment to reduce mutual interference between devices and ensure the normal operation of equipment; wireless communication base stations and antenna systems require wave-absorbing materials to reduce the reflection and scattering of electromagnetic waves and improve communication quality; wave-absorbing materials can be used in building materials to reduce the potential harm of electromagnetic waves to the human body.

[0003] As the requirements for lightweight equipment increase, absorbing materials also need to be lightweight to reduce the impact on the overall weight of the equipment; at the same time, absorbing materials need to have high absorbing efficiency and be able to effectively absorb electromagnetic waves in a wide frequency band; absorbing materials should also be easy to process into various shapes and sizes and achieve mass production to adapt to different application scenarios. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a lightweight, high-efficiency absorbing material based on a water-absorbing resin and a preparation method thereof. The water-absorbing resin is used as a precursor, and a Co@organic resin composite material is obtained by absorbing a certain amount of cobalt salt aqueous solution. Then, the Co@organic resin composite material is pyrolyzed at a certain temperature to obtain a Co / C composite absorbing material. The Co / C composite absorbing material obtained by the method of the present invention has the advantages of strong electromagnetic wave attenuation ability, and is also light and stable.

[0005] The first aspect of the present invention discloses a method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin, comprising the following steps:

[0006] Step S1, preparing a cobalt salt aqueous solution with a concentration of 2-6 g / L, and soaking the water-absorbing resin in the cobalt salt aqueous solution until the color of the solution changes to colorless, thereby obtaining a Co@resin composite material;

[0007] Wherein, the mass ratio of the water-absorbing resin to the cobalt salt is (4-6):(1-3);

[0008] Step S2, pyrolyzing the Co@resin composite material, and then cooling it naturally to obtain a Co / C composite material.

[0009] According to the method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin as described in the first aspect of the present invention, in the step S1, the water-absorbing resin is a polyacrylate-polyacrylamide copolymer.

[0010] According to the method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to the first aspect of the present invention, in the step S1, the cobalt salt is one or more of cobalt chloride, cobalt nitrate, cobalt acetate, and cobalt sulfate.

[0011] According to the method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin as described in the first aspect of the present invention, the cobalt salt is cobalt chloride.

[0012] According to the method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to the first aspect of the present invention, in the step S1, the static soaking time is 24-48 hours.

[0013] According to the method for preparing a lightweight, high-efficiency absorbing material based on a water-absorbing resin as described in the first aspect of the present invention, in the step S2, the heating rate during the pyrolysis is 9-11°C / min, the target temperature is 400-800°C, and the insulation time is 28-32min.

[0014] According to the method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin as described in the first aspect of the present invention, in the step S2, the pyrolysis is performed in an air atmosphere.

[0015] According to the method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to the first aspect of the present invention, in step S2, a tubular furnace is used to pyrolyze the Co@resin composite material.

[0016] According to the method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin as described in the first aspect of the present invention, in the step S2, the Co@resin composite material is crushed and then pyrolyzed.

[0017] The second aspect of the present invention discloses an absorbing material prepared by the aforementioned method for preparing a lightweight and highly efficient absorbing material based on a water-absorbing resin.

[0018] The solution proposed by the present invention has the following technical effects:

[0019] The present invention uses a water-absorbing resin as a precursor, obtains a Co@organic resin composite material by absorbing a certain amount of cobalt salt aqueous solution, and then pyrolyzes the Co@organic resin composite material to obtain a Co / C composite absorbing material; the Co / C composite absorbing material obtained by the method of the present invention has the advantages of strong electromagnetic wave attenuation ability, and is also light and stable.

[0020] In addition, the Co / C composite material prepared by the present invention has strong plasticity, and its phase composition and material structure can be reasonably regulated at the microscopic level by controlling the pyrolysis temperature and the concentration of the cobalt salt, thereby regulating the wave absorbing working frequency band of the Co / C composite material.

[0021] In addition, the preparation technology of the absorbing material of the present invention is green and environmentally friendly. Absorption is carried out in an aqueous environment, and residual Co ions can be fully recovered. The heating environment requirements are low and it is carried out in an air atmosphere. At the same time, no extremely high temperature treatment is required, the cost is low, and it is suitable for large-scale mass production.

[0022] In addition, the absorbing material of the present invention is in powder form and can be added to a suitable medium and evenly applied to the surface of the equipment. It is not limited by the shape of the equipment and is convenient to carry a spare amount with the equipment. The equipment can be reinforced for electromagnetic protection at any time, which can better meet the needs of military applications in harsh environments with rapid changes in temperature and humidity for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 This is a flow chart of a method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to an embodiment of the present invention;

[0025] Figure 2 Transmission electron microscope photographs of the Co / C composite material prepared using 0.2 g of CoCl2 crystals as a reactant according to Example 1 of the present invention at scales of 500 nm (a), 200 nm (b), and 100 nm (c);

[0026] Figure 3 Transmission electron microscope photos of the Co / C composite material prepared using 0.2 g of CoCl2 crystals as a reactant according to Example 2 of the present invention at scales of 100 nm (a), 50 nm (b), and 20 nm (c);

[0027] Figure 4 Transmission electron microscope photos of the Co / C composite material prepared using 0.2 g of CoCl2 crystals as a reactant according to Example 3 of the present invention at scales of 100 nm (a), 50 nm (b), and 20 nm (c);

[0028] Figure 5XRD diagram of Co / C composite material prepared by using 0.2 g CoCl2 crystal as reactant in Example 1(a), Example 2(b) and Example 3(c) of the present invention;

[0029] Figure 6 Graphs of reflection loss of Co / C composite materials prepared using 0 g (a), 0.1 g (b), 0.2 g (c), and 0.3 g (d) CoCl2 crystals as reactants in Example 1 of the present invention;

[0030] Figure 7 Graphs of reflection loss of Co / C composite materials prepared using 0 g (a), 0.1 g (b), 0.2 g (c), and 0.3 g (d) CoCl2 crystals as reactants in Example 2 of the present invention;

[0031] Figure 8 Graphs of reflection loss of Co / C composite materials prepared using 0 g (a), 0.1 g (b), 0.2 g (c), and 0.3 g (d) CoCl2 crystals as reactants in Example 3 of the present invention;

[0032] Fig. 9 Graphs showing reflection loss of the composite materials prepared in Comparative Examples 1, 2 and 3. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] The first aspect of this embodiment discloses a method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin, such as Figure 1 As shown, the following steps are included:

[0035] Step S1, preparing a cobalt salt aqueous solution with a concentration of 2-6 g / L, and soaking the water-absorbing resin in the cobalt salt aqueous solution until the color of the solution changes to colorless, thereby obtaining a Co@resin composite material.

[0036] Step S2, pyrolyzing the Co@resin composite material, and then cooling it naturally to obtain a Co / C composite material.

[0037] In the present invention, the water-absorbing resin is used as a precursor, Co 2+The Co@organic resin composite material is combined with the water-absorbing resin through resin adsorption, and then the Co@organic resin composite material is pyrolyzed to obtain the Co / C composite absorbing material.

[0038] At the same time, the Co / C composite material prepared by the present invention has strong plasticity, and its phase composition and material structure can be reasonably regulated at the microscopic level by controlling the pyrolysis temperature and the concentration of the cobalt salt, thereby further improving the impedance matching and attenuation coefficient of the Co / C composite material, thereby weakening the reflection of the Co / C composite material to electromagnetic waves, making it easier for more electromagnetic waves to enter the internal loss of the Co / C composite material, and achieving the ideal effects of strong absorption, weak reflection, low density and wide bandwidth.

[0039] In step S1, a cobalt salt aqueous solution with a concentration of 2-6 g / L is prepared, and a water-absorbing resin is immersed in the cobalt salt aqueous solution until the color of the solution becomes colorless, thereby obtaining a Co@resin composite material.

[0040] In some embodiments, the mass ratio of the water absorbing resin to the cobalt salt is (4-6):(1-3).

[0041] If the concentration of the cobalt salt aqueous solution is lower than 2 g / L, the Co adsorbed into the water-absorbing resin 2+ If the concentration of cobalt salt solution is higher than 6g / L, the water absorption capacity of the resin will be destroyed due to the acidity and alkalinity of the cobalt salt solution with too high concentration, and the resin will not be able to absorb water and grow, which will greatly reduce the water absorption capacity of the water-absorbing resin to Co. 2+ In addition, the mass ratio of water-absorbing resin to cobalt salt is (4-6):(1-3), which can better achieve Co 2+ Chemical adsorption between water-absorbing resin.

[0042] Specifically, the concentration of the cobalt salt aqueous solution may be 2 g / L, 3 g / L, 4 g / L, 5 g / L, or 6 g / L. Preferably, the concentration of the cobalt salt aqueous solution is 3-5 g / L. Further preferably, the concentration of the cobalt salt aqueous solution is 4 g / L.

[0043] Specifically, the mass ratio of the water-absorbing resin to the cobalt salt may be 4:(1-3), 5:(1-3), or 6:(1-3). Preferably, the mass ratio of the water-absorbing resin to the cobalt salt is 5:2.

[0044] In some embodiments, in step S1, the water-absorbing resin is a polyacrylate-polyacrylamide copolymer.

[0045] In some embodiments, in step S1, the cobalt salt is one or more of cobalt chloride, cobalt nitrate, cobalt acetate, and cobalt sulfate.

[0046] In some embodiments, the cobalt salt is cobalt chloride.

[0047] In some embodiments, in step S1, the static soaking time is 24-48 hours.

[0048] Specifically, the standing and soaking time can be 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, 40h, 42h, 44h, 46h, 48h. Preferably, the standing and soaking time is 24-40h. Further preferably, the standing and soaking time is 24-30h.

[0049] In step S2, the Co@resin composite material is pyrolyzed and then naturally cooled to obtain a Co / C composite material.

[0050] In some embodiments, in step S2, the heating rate during pyrolysis is 9-11°C / min, the target temperature is 400-800°C, and the holding time is 28-32min.

[0051] The target temperature of the pyrolysis of the present invention is 400-800°C. If the temperature is too low, the water-absorbing resin cannot be completely decomposed into carbon, and the obtained material has no absorbing performance; if the temperature is too high, the material is carbonized into CO2 or CO in the air, and the obtained absorbing material is very small. Similarly, if the insulation time is too short, the material does not react completely, and if it is too long, the material gasification phenomenon is serious, and there is little residual material.

[0052] Specifically, the heating rate during the pyrolysis may be 9°C / min, 10°C / min, or 11°C / min. Preferably, the heating rate during the pyrolysis is 10°C / min.

[0053] Specifically, the target temperature during pyrolysis may be 400° C., 450° C., 500° C., 550° C., 600° C., 650° C., 700° C., 750° C., 800° C. Preferably, the target temperature during pyrolysis is 600-800° C. More preferably, the target temperature during pyrolysis is 650-750° C.

[0054] Specifically, the holding time during the pyrolysis can be 28 min, 29 min, 30 min, 31 min, or 32 min. Preferably, the holding time during the pyrolysis is 30 min.

[0055] In some embodiments, in the step S2, the pyrolysis is performed under an air atmosphere.

[0056] In some embodiments, in step S2, a tube furnace is used to pyrolyze the Co@resin composite material.

[0057] In some embodiments, in step S2, the Co@resin composite material is crushed and then pyrolyzed.

[0058] The second aspect of this embodiment discloses an absorbing material prepared by the aforementioned method for preparing a lightweight and high-efficiency absorbing material based on a water-absorbing resin.

[0059] Example 1

[0060] (1) 0.1 g CoCl2, 0.2 g CoCl2 and 0.3 g CoCl2 were respectively added into 50 ml deionized water and stirred thoroughly to obtain three aqueous cobalt salt solutions with different concentrations.

[0061] (2) Weigh four portions of 0.4-0.6 g of polyacrylate-polyacrylamide copolymer and add them into the above three different concentrations of cobalt salt aqueous solutions and 50 ml of deionized water without cobalt salt, respectively, and soak them for 24 hours to obtain four Co@resin composite materials containing different amounts of cobalt ions.

[0062] (3) The above four Co@resin composite materials containing different amounts of cobalt ions were crushed and placed in a porcelain boat. The porcelain boat containing the Co@resin composite materials was then placed in a tubular furnace for pyrolysis. The heating rate was set at 10°C / min. The temperature was raised to 400°C in an air atmosphere and then kept at that temperature for 30 min. The temperature was then naturally cooled to obtain four Co / C composite materials, which were numbered as Example 1-Co0, Example 1-Co 0.1 , Example 1-Co 0.2 , Example 1-Co 0.3 .

[0063] Example 2

[0064] The difference from Example 1 is that the target temperature during pyrolysis is 600°C.

[0065] Example 3

[0066] The difference from Example 1 is that the target temperature during pyrolysis is 800°C.

[0067] Comparative Example 1

[0068] (1) Add 0.2 g AlCl3 into 50 ml deionized water and stir thoroughly to obtain an aluminum salt aqueous solution.

[0069] (2) Weigh 0.4-0.6 g of polyacrylate-polyacrylamide copolymer and add it to an aluminum salt aqueous solution, and let it stand and soak for 24 hours to obtain an Al@resin composite material.

[0070] (3) The Al@resin composite material was crushed and placed in a porcelain boat, and then the porcelain boat containing the Al@resin composite material was placed in a tubular furnace for pyrolysis. The heating rate was set to 10°C / min, and the temperature was raised to 600°C in an air atmosphere and then kept at this temperature for 30 minutes, and then naturally cooled to obtain a sample numbered as Comparative Example 1-Al 0.2 Al / C composite materials.

[0071] Comparative Example 2

[0072] The difference from Comparative Example 1 is that the metal salt is ZnCl2, and the obtained product is numbered as Comparative Example 2-Zn 0.2 Zn / C composites.

[0073] Comparative Example 3

[0074] The difference from Comparative Example 1 is that the metal salt is NiCl2, and the obtained product is numbered as Comparative Example 3-Ni 0.2 Ni / C composite materials.

[0075] Figure 2 The transmission electron microscope images of the Co / C composite material prepared with 0.2 g of CoCl2 crystal as the reactant according to Example 1 of the present invention are taken at 500 nm (a), 200 nm (b), and 100 nm (c) scales. Figure 2 It can be seen that at the pyrolysis temperature of 400 °C, the particle size of Co-containing nanocrystals is generally between 150-200 nm and is loaded on the carbon layer.

[0076] Figure 3 The transmission electron microscope images of the Co / C composite material prepared with 0.2 g of CoCl2 crystal as the reactant according to Example 2 of the present invention are taken at 100 nm (a), 50 nm (b), and 20 nm (c) scales. Figure 3 It can be seen that at the pyrolysis temperature of 600°C, the particle size of the Co-containing nanocrystals is significantly reduced to between 50-100 nm; as the particle size decreases, the distribution of the Co-containing nanocrystals tends to be uniform, and at the same time, the thickness of the carbon layer supporting the Co-containing nanocrystals becomes significantly thinner.

[0077] Figure 4 The transmission electron microscope photos of the Co / C composite material prepared with 0.2g CoCl2 crystal as the reactant according to Example 3 of the present invention at 100nm (a), 50nm (b), and 20nm (c) scales. Figure 4 It can be seen that at the pyrolysis temperature of 800°C, extremely fine Co-containing nanocrystals uniformly loaded on a thin layer of carbon are generated, with a particle size between 1 and 5 nm.

[0078] Under the high temperature condition of 400℃, the upper limit of high temperature is not very high. Therefore, during the pyrolysis of Co@resin composite materials, the nucleation rate of Co nanocrystals is not high. During the pyrolysis process, under the condition of less nuclei, Co 2+ As the heat treatment temperature rises to 600℃ and 800℃, the supercooling degree of the pyrolysis process is improved, so the nucleation rate of Co-containing nanocrystals also increases. With more Co-containing nuclei, the Co-containing nanocrystals participating in the growth of the nuclei are larger. 2+ The number of nanocrystals is relatively small, so the size of the obtained nanocrystals is reduced. Smaller Co nanocrystals can achieve richer Co / C interfaces, thereby improving the dielectric loss capacity of the material and improving the material's microwave absorption performance.

[0079] Figure 5 The XRD diagram of the Co / C composite material prepared using 0.2 g of CoCl2 crystals as a reactant in Example 1(a), Example 2(b), and Example 3(c) of the present invention. Figure 5It can be seen that the peaks of the Co / C composite material obtained in Example 1 at 2θ angles of 19.000°, 31.271°, 36.845°, 38.423°, 44.808°, 55.655°, 59.353°, 65.231°, 77.338° and 78.403° belong to Co3O4 (standard PDF card number 43-1003), so the Co in the Co / C composite material obtained in Example 1 mainly exists in the magnetic Co3O4. The peaks with 2θ angles of 19.000°, 31.271°, 36.845°, 44.808°, 55.655°, 65.231°, 74.117°, 77.338°, and 78.403° for the Co / C composite material obtained in Example 2 belong to Co3O4 (standard PDF card number 43-1003); the peaks with 2θ angles of 16.131° and 32.411° belong to CoC8 (standard PDF card number 51-0625); the peaks with 2θ angles of 38.183°, 41.451°, 46.711°, and 59.236° belong to Co3C (standard PDF card number 51-0625). The peaks of 2θ angles of the Co / C composite material obtained in Example 3 are 19.000°, 31.271°, 36.845°, 44.808°, 55.655°, 65.231°, 74.117°, 77.338°, and 78.403°, which belong to Co3O4 (standard PDF card number 43-1003); the peaks of 2θ angles of 16.131° and 32.411° belong to CoC8 (standard PDF card number 51-0625); the peaks of 2θ angles of 38.183°, 41.451°, 46.711°, and 59.236° belong to Co3C (standard PDF card number 51-0625). Therefore, Co in the Co / C composite material obtained in Example 2 and Example 3 is simultaneously present in Co3O4, CoC8, and Co3C.

[0080] Figure 6 The reflection loss diagram of Co / C composite material prepared by using 0g (a), 0.1g (b), 0.2g (c), and 0.3g (d) CoCl2 crystal as reactants in Example 1 of the present invention. The frequency range in which the reflection loss is less than -10dB is usually called the effective absorption bandwidth. Figure 6 It can be seen that at a pyrolysis temperature of 400°C, when the thickness of the non-Co-doped composite material is less than 1.85 mm, effective electromagnetic loss cannot be achieved. As the thickness gradually increases, effective electromagnetic wave absorption can be achieved within a smaller bandwidth. 0.1The effective bandwidth and reflection loss peak of the sample are significantly improved compared with pure carbon materials. In all thickness ranges greater than 1.75 mm, they have strong electromagnetic wave attenuation capabilities in the 11.5-13, 13.5-14, 15-16, and 17.5-18 GHz frequency bands. The reflection loss of 2.25 mm thickness reaches a peak of -40.81 dB at 12 GHz, which can almost completely attenuate electromagnetic waves. As the Co concentration increases, Example 1-Co 0.2 and Example 1-Co 0.3 The electromagnetic wave attenuation performance of the sample is seriously reduced, and the effective absorption bandwidth is narrow. This shows that at a pyrolysis temperature of 400°C, the addition of a small amount of Co element can significantly improve the electromagnetic wave attenuation performance. As the amount of Co element increases, it has a side effect on the performance, which is even lower than that of Example 1-Co0 sample.

[0081] Figure 7 The reflection loss diagram of Co / C composite material prepared by using 0g (a), 0.1g (b), 0.2g (c), and 0.3g (d) CoCl2 crystal as reactant in Example 2 of the present invention. Figure 7 It can be seen that at a pyrolysis temperature of 600°C, Example 2-Co0, Example 2-Co 0.1 The samples almost have no effective absorption bandwidth and poor electromagnetic wave attenuation performance, indicating that at this temperature, the addition of a small amount of Co element cannot effectively improve the electromagnetic wave attenuation ability of the Co / C composite material. However, with the increase of Co element, the reflection loss ability has been significantly improved. Example 2-Co 0.2 The effective absorption bandwidth of the sample is 4.5 GHz in the thickness range of 1.75-2.45 mm; in particular, when the thickness is 2.15 mm, the effective absorption bandwidth is 6 GHz, and at a frequency of 13.28 GHz, the reflection loss peak is -44.85 dB. 0.3 The sample also has excellent wave absorption performance in the high frequency range, and can effectively absorb electromagnetic waves in the range of 14.5GHz-18GHz. In the thickness range of 1.85-2.45mm, the effective absorption bandwidth reaches above 4.5GHz; in particular, the effective bandwidth of the 2.35mm thick sample reaches 6.6GHz. At a frequency of 16.16GHz, the minimum reflection loss of the 1.95mm thick sample reaches -42.65dB.

[0082] Figure 7 and Figure 6 By comparison, there is a large difference in reflection loss performance between samples at 600°C and 400°C pyrolysis temperatures, indicating that temperature has a great influence on the electromagnetic wave absorption capacity of the prepared Co / C composite material.

[0083] Figure 8The reflection loss diagram of the Co / C composite material prepared with 0g (a), 0.1g (b), 0.2g (c), and 0.3g (d) CoCl2 crystals as reactants in Example 3 of the present invention. Figure 8 It can be seen that at a pyrolysis temperature of 800°C, when the thickness of the Example 3-Co0 sample reaches more than 2.25 mm, a wide effective absorption bandwidth of about 4 GHz can be achieved in the high frequency region (13-18 GHz). The addition of the Co element will significantly improve the electromagnetic wave absorption performance. 0.1 In the medium and high frequency (8-16GHz) region, the sample has an effective absorption bandwidth of about 4GHz in the thickness range of 1.75mm-2.45mm. As the thickness increases, the thickness above 2.25mm has good absorption performance in the range of 6-7GHz, and when the thickness is 2.35mm, the reflection loss at the frequency of 12GHz reaches -37.65dB. 0.2 The sample's wave absorption performance shifts to low frequencies. When the thickness ranges from 1.75mm to 2.05mm, the wave absorption frequency band is concentrated in the X-band. When the thickness ranges from 2.05mm to 2.45mm, the ability to attenuate electromagnetic waves is prominent at 6-7.5GHz. When the thickness is 2.45mm, the reflection loss at 6.5GHz reaches -28.21dB. 0.3 The sample's absorbing ability is mainly reflected in the X-band range, but the effective absorption bandwidth is relatively narrow, basically around 1.2-1.5GHz.

[0084] Compared with Example 1, the types of Co compounds obtained in Example 2 and Example 3 are richer, and the nanocrystals are also finer. The rich Co compounds can effectively improve the magnetic loss capacity of the material. At the same time, the rich Co / C interface can also effectively regulate the electromagnetic parameters of the Co / C composite material, thereby achieving efficient wave absorption in a specific frequency band. By comparing the reflection loss graph, it can be seen that compared with Example 1-Co 0.2 Sample, Example 2-Co 0.2 Samples and Examples 3-Co 0.2 The sample has stronger reflection loss and adjustable wave absorption frequency band.

[0085] Fig. 9 Graphs showing the reflection loss of the composite materials prepared in Comparative Examples 1, 2 and 3. Fig. 9It can be seen that compared with Example 2, the reflection loss performance of the Co-containing composite material is much stronger than that of the Al, Zn or Ni-containing composite materials at the same thickness. This is because Co is a magnetic metal, which can achieve both electrical loss and magnetic loss in terms of electromagnetic wave loss; while Al and Zn in the comparative example are not magnetic metals, so the electromagnetic wave loss is mainly through electrical loss, and the loss mechanism is limited. Although Ni is a magnetic metal, the pH of its Ni salt solution does not match the pH required for the adsorption of the absorbent resin. Therefore, compared with Co salt, Ni salt cannot be effectively adsorbed, resulting in insufficient absorption capacity of the composite material derived from it.

[0086] Example 4

[0087] The difference from Example 2 is that the heating rate during pyrolysis is 9° C. / min and the holding time is 28 min.

[0088] Example 5

[0089] The difference from Example 2 is that the heating rate during pyrolysis is 11° C. / min and the holding time is 29 min.

[0090] Example 6

[0091] The difference from Example 2 is that the holding time during the pyrolysis is 31 minutes.

[0092] Example 7

[0093] The difference from Example 2 is that the holding time during the pyrolysis is 32 minutes.

[0094] In summary, the solution proposed by the present invention has the following technical effects:

[0095] The present invention uses a water-absorbing resin as a precursor, obtains a Co@organic resin composite material by absorbing a certain amount of cobalt salt aqueous solution, and then pyrolyzes the Co@organic resin composite material to obtain a Co / C composite absorbing material; the Co / C composite absorbing material obtained by the method of the present invention has the advantages of strong electromagnetic wave attenuation ability, and is also light and stable.

[0096] In addition, the Co / C composite material prepared by the present invention has strong plasticity, and its phase composition and material structure can be reasonably regulated at the microscopic level by controlling the pyrolysis temperature and the concentration of the cobalt salt, thereby regulating the wave absorbing working frequency band of the Co / C composite material.

[0097] In addition, the preparation technology of the absorbing material of the present invention is green and environmentally friendly. Absorption is carried out in an aqueous environment, and residual Co ions can be fully recovered. The heating environment requirements are low and it is carried out in an air atmosphere. At the same time, no extremely high temperature treatment is required, the cost is low, and it is suitable for large-scale mass production.

[0098] In addition, the absorbing material of the present invention is in powder form and can be added to a suitable medium and evenly applied to the surface of the equipment. It is not limited by the shape of the equipment and is convenient to carry a spare amount with the equipment. The equipment can be reinforced for electromagnetic protection at any time, which can better meet the needs of military applications in harsh environments with rapid changes in temperature and humidity for a long time.

[0099] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin, characterized in that: The steps include: Step S1, preparing a cobalt salt aqueous solution with a concentration of 2-6 g / L, and soaking the water-absorbing resin in the cobalt salt aqueous solution until the color of the solution changes to colorless, thereby obtaining a Co@resin composite material; Wherein, the mass ratio of the water-absorbing resin to the cobalt salt is (4-6):(1-3); Step S2, pyrolyzing the Co@resin composite material, and then cooling it naturally to obtain a Co / C composite material.

2. The method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to claim 1, characterized in that: In the step S1, the water-absorbing resin is a polyacrylate-polyacrylamide copolymer.

3. The method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to claim 1, characterized in that: In the step S1, the cobalt salt is one or more of cobalt chloride, cobalt nitrate, cobalt acetate, and cobalt sulfate.

4. The method for preparing a light and efficient wave absorbing material based on a water-absorbing resin according to claim 3, characterized in that: The cobalt salt is cobalt chloride.

5. The method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to claim 1, characterized in that: In the step S1, the static soaking time is 24-48 hours.

6. The method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to claim 1, characterized in that: In the step S2, the heating rate during the pyrolysis is 9-11°C / min, the target temperature is 400-800°C, and the holding time is 28-32min.

7. The method for preparing a light and efficient wave absorbing material based on a water-absorbing resin according to claim 1, characterized in that: In the step S2, the pyrolysis is performed under an air atmosphere.

8. The method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to claim 1, characterized in that: In the step S2, a tube furnace is used to pyrolyze the Co@resin composite material.

9. The method for preparing a lightweight, high-efficiency wave-absorbing material based on a water-absorbing resin according to claim 1, characterized in that: In the step S2, the Co@resin composite material is crushed and then pyrolyzed.

10. A microwave absorbing material prepared by the method for preparing a lightweight and efficient microwave absorbing material based on a water-absorbing resin according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Wave absorbing material and forming method thereof

    CN105269911A

  • Co / C composite electromagnetic absorbing agent and preparation method thereof

    CN108377638A

  • Preparation method of porous carbon and carbon-supported catalyst

    CN113648987A

  • Magnetic biomass carbon-based composite material, metamaterial microwave absorber and preparation method and application of magnetic biomass carbon-based composite material and metamaterial microwave absorber

    CN116435081A

  • Core-shell structure polymer particle with wrinkled surface as well as preparation method and application of core-shell structure polymer particle

    CN118530494A